Effective Strategies for Managing Wheat Diseases: Mapping Academic Literature Utilizing VOSviewer and Insights from Our 15 Years of Research - Ioannis Vagelas (Agrochemicals)
Wheat pathogens pose a significant risk to global wheat production, with climate change further complicating disease dynamics. Effective management requires a combination of genetic resistance, cultural practices, and careful use of chemical controls. Ongoing research and adaptation to changing environmental conditions are crucial for sustaining wheat yields and food security. Based on selective academic literature retrieved from the Scopus database and analyzed by a bibliographic software such as the VOSviewer we discussed and focused on various aspects of current and future strategies for managing major wheat pathogens and diseases such as Tan spot, Septoria tritici blotch, Fusarium head blight, etc. Chemical management methods, such as the use of fungicides, can be effective but are not always preferred. Instead, agronomic practices like crop rotation and tillage play a significant role in managing wheat diseases by reducing both the incidence and severity of these diseases. Moreover, adopting resistance strategies is essential for effective disease management.